Analysis Factor of Efforts to Prevent High Risk of Pregnancy in pregnant women through the Family Centered Empowerment theory approach in regional puskesmas Tuban County - Puspitadewi, Teresia Retna; Nugraheni, Wahyuningsih Triana; Lontaan, Anita (Media Keperawatan Indonesia, 2025)
Data from two puskesmas in Tuban Regency with the number of high-risk pregnant women, namely the Merak Urak Health Center, in 2019-2020 obtained 104 pregnant women, and the Palang Health Center obtained 213 pregnant women. This figure has not reached the target of the 2015 MDGs of 102 per 100,000 live births and the 70 per 100,000 live births of the SDGs target in 2030. The research aims to determine the dominant factors of efforts to prevent high-risk pregnancy in pregnant women through the Family Centered Empowerment theory approach. The research design is a correlational, descriptive, cross-sectional approach. The population of all pregnant women in the working area of the Merak Urak Health Center and the Palang Health Center in Tuban Regency. The sample size uses the rule of thumb in SEM; with the maximum likelihood method, a sample of at least 150 respondents.Data collection using questionnaires was then tabulated in distribution tables and analyzed with uji statistical univariate analysis for frequency and percentage distribution and bivariate analysis with the logistic regression test to analyze the dominant factor.The results of this study are meaningful results on efforts to prevent high-risk pregnancy, namely interpersonal factors (p = 0.000) and cognitive factors (p = 0.002), based on multivariate analysis of dominant factors, which influence prevention efforts in high-risk women. Interpersonal factors are more influential than cognitive factors (OR interpersonal factors > OR cognitive factors). It can be concluded that interpersonal factors can influence the decision to prevent pregnancy.